The new illustrated space encyclopedia. - Bergaust, Erik (Putnam, 1970)
Defines 2000 astronautical terms. Includes biographies of astronauts, specifications of major United States booster rockets, a log of space projects, tables of planets and satellites, and information on various space programs.